1990
DOI: 10.1128/aem.56.9.2717-2725.1990
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Stable Bdelloplasts as a Starvation-Survival Strategy of Marine Bdellovibrios

Abstract: Several wild-type isolates of marine bdellovibrios formed stable bdelloplasts when they infected gramnegative bacterial prey under certain culture conditions. Synchronous predator-prey cultures and low nutrient concentrations increased the yield of stable bdelloplasts. The bdellovibrio cells retained in the stable bdelloplasts showed a high survival capacity in nutrient-depleted saline solution (10% viable Bdellovibrio cells after 3 months at 25°C), whereas Bdellovibrio attack-phase cells kept under the same s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 20 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…Markelova also suggested that under unfavorable conditions B. bacteriovorus cells are able to persist inside surface-attached bdelloplasts, which protect them from the environment. The formation of stable bdelloplasts as a survival strategy was in agreement with previous studies by Sánchez-Amat and Torrella (1990). Another wastewater pollutants that might have an impact on Delta-BALOs are surfactants.…”
Section: Potential Limitationssupporting
confidence: 91%
“…Markelova also suggested that under unfavorable conditions B. bacteriovorus cells are able to persist inside surface-attached bdelloplasts, which protect them from the environment. The formation of stable bdelloplasts as a survival strategy was in agreement with previous studies by Sánchez-Amat and Torrella (1990). Another wastewater pollutants that might have an impact on Delta-BALOs are surfactants.…”
Section: Potential Limitationssupporting
confidence: 91%
“…Dependence on phagotrophy can often result in starvation due to unstable food source. Therefore, certain predatory bacteria have developed specific resting forms to resist starvation 23,29 . However, we were unable to observe any ‘ Ca .…”
Section: Resultsmentioning
confidence: 99%
“…Ideally, Bdellovibrio strains could be found in every site where Gram-negative bacteria, representing their food supply, are present [ 35 , 37 , 38 , 40 , 43 , 44 , 45 , 46 , 47 , 48 ]. Predators seem to play an essential role as ecological balancers in the environment, shaping the microbial community [ 49 , 50 , 51 , 52 , 53 ]. As the knowledge of these microorganisms has increased, the diversity among isolates has required the classification of some groups into distinct species and genera.…”
Section: Discovery Of Predators and Characteristicsmentioning
confidence: 99%